2013
DOI: 10.1371/journal.pone.0055628
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Shape Changes Are Induced by Knockdown of the SWI/SNF ATPase BRG1 and Are Independent of Cytoskeletal Connections

Abstract: Changes in nuclear morphology occur during normal development and have been observed during the progression of several diseases. The shape of a nucleus is governed by the balance of forces exerted by nuclear-cytoskeletal contacts and internal forces created by the structure of the chromatin and nuclear envelope. However, factors that regulate the balance of these forces and determine nuclear shape are poorly understood. The SWI/SNF chromatin remodeling enzyme ATPase, BRG1, has been shown to contribute to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 71 publications
4
58
0
Order By: Relevance
“…However, changes in nuclear shape can be induced from either external forces exerted by the cytoskeleton or via internal nuclear forces. Previous work showed that SMARCA4 knockdown results in nuclear shape alterations in MCF-10A cells (Imbalzano et al 2013b). However, the disruption of the cytoplasmic filaments (actin, tubulin, and cytokeratins) did not alter SMARCA4-dependent structural changes observed in the MCF-10A cells (Imbalzano et al 2013b).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, changes in nuclear shape can be induced from either external forces exerted by the cytoskeleton or via internal nuclear forces. Previous work showed that SMARCA4 knockdown results in nuclear shape alterations in MCF-10A cells (Imbalzano et al 2013b). However, the disruption of the cytoplasmic filaments (actin, tubulin, and cytokeratins) did not alter SMARCA4-dependent structural changes observed in the MCF-10A cells (Imbalzano et al 2013b).…”
Section: Discussionmentioning
confidence: 96%
“…Previous work showed that SMARCA4 knockdown results in nuclear shape alterations in MCF-10A cells (Imbalzano et al 2013b). However, the disruption of the cytoplasmic filaments (actin, tubulin, and cytokeratins) did not alter SMARCA4-dependent structural changes observed in the MCF-10A cells (Imbalzano et al 2013b). This implies that SMARCA4, apart from its chromatin remodeling function, might have additional roles in maintaining the structural integrity of the nucleus (Imbalzano et al 2013a).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The results of previous studies show there is a continuum of biological elements which establish a mechano-transduction cascade linking membrane displacements to cytoskeletal filaments, the nucleus and sub-nuclear structures, and cell integrin-substrate forces [27,28]. Thus, the biomechanical measurements cannot be assigned to a particular sub-structure, but dominated by the response of a sub-cellular structural domain.…”
Section: Discussionmentioning
confidence: 99%
“…Second, Pap is a multichromatic cell stain, and the combination of colors highlights many different features of cellular structures, including chromatin condensation and cytokeratin expression. [32][33][34] In Pap-or DAPI-stained images, aberrant nuclear and chromatin structures were detected in lamin A/C knockdown cells (Fig. 1A and B).…”
Section: Cellular Morphology Changes Upon Depletion Of Nuclear Membramentioning
confidence: 99%